FIGURE 13 in Description of Oromurcia magadanensis sp. nov. (Acari, Oribatida, Ceratozetidae) from Russia, with remarks on biogeography of the genus Oromurcia Thor, 1930 - Ermilov, Sergey G.; Makarova, Olga L.; Behan-Pelletier, Valerie M. (Zenodo, 2022)
FIGURE 13. Variability of some prodorsal structures in individuals of Oromurcia bicuspidata from Kolguev Island, Barents Sea. A–I—anterior part of prodorsum, setae shown partially; J—variability of rostrum; K—variability of bothridial seta. Scale bar 50 μm. Published as part of Ermilov, Sergey G., Makarova, Olga L. & Behan-Pelletier, Valerie M., 2022, Description of Oromurcia magadanensis sp. nov. (Acari, Oribatida, Ceratozetidae) from Russia, with remarks on biogeography of the genus Oromurcia Thor, 1930, pp. 30-52 in Zootaxa 5187 (1) on page 48, DOI:10.11646/zootaxa.5187.1.5, http://zenodo.org/record/7078260